Transarterial Chemoembolization of Hepatocellular Carcinoma with Idarubicin-Loaded Tandem Drug-Eluting Embolics - Guiu, Boris (Cancers (Basel), 2019)
Objective: To describe the responses, toxicities and outcomes of HCC patients treated by transarterial chemoembolization (TACE) using idarubicin-loaded TANDEM beads. Materials and Methods: Seventy-two consecutive patients (mean age: 71 years (58–84 years)) with HCC were treated by TACE using idarubicin-loaded TANDEM in a first line, over a five-year period. Most patients (89%) had liver cirrhosis classified as Child–Pugh A (90%). BCLC B classification applied in 85% of cases. Baseline tumor burden was limited to one to three nodules in 92% of cases, unilobar in 88% cases, with a median tumor diameter of 55 mm (range: 13–150 mm). Toxicity was assessed using NCI CTC AE v4.0. Response was assessed using mRECIST criteria. Time-to-treatment failure (TTTF) and overall survival (OS) were also calculated based on Kaplan–Meier method. Result: Of 141 TACE sessions performed with bead sizes of 100 and 75 µm in 42 (29.8%) and 99 (70.2%) sessions, respectively. In 78% of all TACE sessions, the full dose of idarubicin-loaded beads was injected. Grade 3–4 AE were observed after 73 (52%) sessions, most of them being biological. Multi-organ failure was observed three days after the first TACE in a Child B patients, unfortunately leading to death. Overall, the best objective response rate (ORR) was 65%. Median follow-up lasted 14.3 months (95% CI: 11.2–18.8 months). Median TTTF and OS were 14.4 months (95% CI: 7.2–24.6 months) and 34.6 months (95% CI: 24.7—not reached) respectively. Conclusion: In this retrospective study involving well-selected HCC patients, high ORR and long TTTF and OS are observed after TACE using idarubicin-loaded TANDEM. A randomized trial is needed.